If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -10)(4x + -9) = 0 Reorder the terms: (-10 + 6x)(4x + -9) = 0 Reorder the terms: (-10 + 6x)(-9 + 4x) = 0 Multiply (-10 + 6x) * (-9 + 4x) (-10(-9 + 4x) + 6x * (-9 + 4x)) = 0 ((-9 * -10 + 4x * -10) + 6x * (-9 + 4x)) = 0 ((90 + -40x) + 6x * (-9 + 4x)) = 0 (90 + -40x + (-9 * 6x + 4x * 6x)) = 0 (90 + -40x + (-54x + 24x2)) = 0 Combine like terms: -40x + -54x = -94x (90 + -94x + 24x2) = 0 Solving 90 + -94x + 24x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(45 + -47x + 12x2) = 0 Factor a trinomial. 2((5 + -3x)(9 + -4x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(5 + -3x)' equal to zero and attempt to solve: Simplifying 5 + -3x = 0 Solving 5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 0 + -5 -3x = 0 + -5 Combine like terms: 0 + -5 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667Subproblem 2
Set the factor '(9 + -4x)' equal to zero and attempt to solve: Simplifying 9 + -4x = 0 Solving 9 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = 0 + -9 -4x = 0 + -9 Combine like terms: 0 + -9 = -9 -4x = -9 Divide each side by '-4'. x = 2.25 Simplifying x = 2.25Solution
x = {1.666666667, 2.25}
| 2x^2+10x-85=0 | | x-6=9-4x | | 2n^2+25n+63=0 | | 14-(-8x)+4x-(-12)= | | 3(b+4)+b=-6(3+b) | | 7n^2+6n+42=0 | | 7x-(6x+8)=3x-46 | | 11+3x-7=6x-5-3x | | 2w+10=22 | | 2+3(2-5)-8=2(x-5) | | 1.5x-0.5y=12 | | -1=1/3x-6 | | 4x+8=2(5+2x) | | 4x+8=2(5+2x)7 | | 2a-9=5a-12 | | 0=2-5x+y | | 7x-4=6x+7 | | 1.3x+5y=20 | | 2v+5v+3= | | A=P+PRTfort | | −2/5y=4 | | 10x+12=-8 | | -16x^2+40x+24=0 | | 2-3(x-4)-3x=3-2(x-3)+6(1-x) | | −2/5y=4. | | -2-x=-2y | | 7K+5=-37 | | 3x+24=4x+24 | | 3x-2y+3z=12 | | -9y=12x | | X^3+x=27000 | | -3(x+5)+6(3x-4)=7(x+3)-(2x+6) |